Properties of Thiol-ene Photocurable Highly Hydrophobic and Oleophobic Nanocomposite Coatings on ABS and HIPS Substrates - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR (WILEY-HINDAWI, 2013)
In this study, thiolene photocurable highly hydrophobic and oleophobic coatings were prepared and characterized. Trimethylolpropane tris(3-mercaptopropionate) and triallyl 1,3,5-triazine-2,4,6(1H,3H,5H)-trione were used for the preparation of the base formulation. Highly hydrophobic and oleophobic coatings were prepared with the aid of a fluorinated acrylate (Fluowet AC 812) and hydrophobic-fumed nanosilica particles. Nanoparticles were added for increasing the surface roughness and also to increase thermal and mechanical properties of the coatings. Coatings were applied on ABS (acrylonitrilebutadienestyrene) and HIPS (high impact polystyrene) substrates. As the fluorine and nanosilica contents were increased in the formulations, flame retardancy, hydrophobicity, and the oleophobicity of the coatings increased. Coatings were found to be highly thermally stable, highly solvent, and chemically resistant. The surface roughness of the coatings increased with the addition of hydrophobic-fumed nanosilica particles. In addition, the relation between the surface energy and the contact angle of the coatings was investigated. (c) 2012 Wiley Periodicals, Inc. Adv Polym Techn 32: E416E426, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/adv.21289
Keywords: Coatings; Hydrophobe; Radical polymerization; Silicas; Thiolene; SURFACE MODIFICATION; PHOTOPOLYMERIZATION; KINETICS; MONOMERS; SYSTEMS; RESIN; FILMS; WATER